IDENTIFIKASI LEVEL KAPABILITAS IT GOVERNANCE MENGGUNAKAN FRAMEWORK COBIT 2019 PADA PT XYZ - Cherry Lumingkewas; Maestro Phytagoras; Virjin Fanesa; Michelle Walangitan; Joe Yuan Yulian Mambu; Erienika Lompoliu (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2022)
There are numerous frameworks that can be utilized to develop information technology governance when examining corporate governance. COBIT is an auditing framework that auditors use to control and manage IT governance. PT. XYZ is a newcomer in the paint and coating production industry in Indonesia, and to compete with competitors and accommodate corporate goals, a design in IT Governance is required to determine what must be changed. The research aimed to provide an IT governance design that tailored based on what the company needs. The governance design is compiled by using the latest COBIT 2019 framework, which involved interview and quantification of each Design Factor values from the interview. We conducted interviews with prominent IT personnel within the company using the COBIT 2019 framework Design Factor (DF), which includes: enterprise strategy, enterprise goals, risk profile, and I&T related issues, threat landscape, compliance requirement, role of IT, model of IT, and finally IT implementation methods. The results suggest that five core models, including EDM05, APO06, APO14, MEA03, and MEA04, are advised to have a competency level of 2. There is one core model for which a skill level of 3 is indicated, which is BAI09. This study is only concerned with developing an IT governance design; there is no evaluation of the core model or methodology.